1996
DOI: 10.1111/j.1476-5381.1996.tb15767.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple prejunctional actions of angiotensin II on noradrenergic transmission in the caudal artery of the rat

Abstract: 1 Angiotensin II produced concentration-dependent enhancement of both stimulation-induced (S-I) efflux of [3H]-noradrenaline and stimulation-evoked vasoconstrictor responses in isolated preparations of rat caudal artery in which the noradrenergic transmitter stores had been labelled with [3H]-noradrenaline.The threshold concentrations of angiotensin II for enhancement of S-I efflux (between 0.03 and 0.1 gM) and of the stimulation-evoked vasoconstrictor responses (about 0.3 gM) were 10-1000 times higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
29
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
6
29
0
1
Order By: Relevance
“…Thus, we suggested that the prejunctional receptor subserving the enhancement of transmitter noradrenaline release in this tissue had characteristics similar to the ATIB binding site described by Zhou et al (1993). In contrast, the receptor subtype subserving the direct vasoconstrictor actions of angiotensin II in the rat caudal artery was found to be sensitive to losartan but not PD 123319 (Cox et al, 1995), which is consistent with results from other studies (Rhaleb et al, 1991).In our studies with isolated caudal artery preparations from a normotensive (Sprague-Dawley) strain of rat, we found that, compared to published findings in other tissues, angiotensin II had a relatively low potency in respect of its ability to enhance stimulation-induced (S-I) [3H]-noradrenaline efflux (Cox et al, 1996). In addition, a striking and unexpected finding of those studies was that the enhancement of S-I [3H]-noradrenaline efflux and of the associated vasoconstrictor responses produced by angiotensin II, in a concentration just above threshold (0.1 /iM), was greatly increased in the presence of 0.01 gM losartan.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…Thus, we suggested that the prejunctional receptor subserving the enhancement of transmitter noradrenaline release in this tissue had characteristics similar to the ATIB binding site described by Zhou et al (1993). In contrast, the receptor subtype subserving the direct vasoconstrictor actions of angiotensin II in the rat caudal artery was found to be sensitive to losartan but not PD 123319 (Cox et al, 1995), which is consistent with results from other studies (Rhaleb et al, 1991).In our studies with isolated caudal artery preparations from a normotensive (Sprague-Dawley) strain of rat, we found that, compared to published findings in other tissues, angiotensin II had a relatively low potency in respect of its ability to enhance stimulation-induced (S-I) [3H]-noradrenaline efflux (Cox et al, 1996). In addition, a striking and unexpected finding of those studies was that the enhancement of S-I [3H]-noradrenaline efflux and of the associated vasoconstrictor responses produced by angiotensin II, in a concentration just above threshold (0.1 /iM), was greatly increased in the presence of 0.01 gM losartan.…”
supporting
confidence: 70%
“…[3H]-noradrenaline present in the perfusate/superfusate collection was separated chromatographically from its tritiated metabolites and measured by liquid scintillation counting (Cox et al, 1996). noradrenaline were determined, again, as previously described (Cox et al, 1996), the second period of stimulation in each case being expressed as a percentage of the corresponding value for the first period of stimulation (% R2/R1 and % S2/S1, respectively).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations